(untitled) (Heritage, 2021)
In this paper, we will try to outline the letters on the old monuments in the Golija Mountain villages of Ljuljac and Kuzmičevo and compare them with the Nišan tombstones in the village of Škrijelje on the slopes of Pešter. All the monuments that were the subject of this analysis date from the 19th century. The main goal of the research is to determine the graphic circumstances and the relationships of the three alphabets (Cyrillic, Old Turkish / Ottoman alphabet and Latin) and their status in the mentioned period. In addition, the paper points out the sociolinguistic review of the graphic shift on Muslim monuments. The article also gives a brief overview of anthroponyms that appear on all tombstones.